Pengaruh Pembelajaran Berbasis Proyek Dalam Kurikulum Merdeka Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PAI - Husnan Sulaiman; Sani Nisfia Nursiyam (MASAGI : Jurnal Pendidikan Agama Islam, 2026)
Creating a conducive and well-maintained school environment to support learning and foster an environmentally conscious character. Observations at Al-Hikmah Tarogong Kaler Junior High School, Garut, showed that students did not fully understand the concept of environmental conservation, were inconsistent in their environmental stewardship, and lacked skills in environmental maintenance practices. This situation demonstrates the need for an innovative learning model that not only enhances knowledge but also fosters active and independent student attitudes and skills. Previous research has shown that project-based learning effectively improves learning outcomes focused on Mathematics. The novelty of this research lies in the application of project-based learning to Islamic Religious Education (PAI) subjects within the Independent Curriculum, emphasizing cognitive, affective, and psychomotor aspects. The application of project-based learning with the theme "Conserving Nature and Protecting Life" in PAI Phase D aims to develop cognitive, affective, and psychomotor aspects in an integrated manner. The method used was descriptive quantitative with 70 students as respondents. Data were collected through observation, interviews, documentation, and questionnaires, analyzed using multiple linear regression using SPSS version 26. The results showed that project-based learning had a 33% effect on cognitive learning outcomes, a 16.4% effect on affective learning outcomes, and a 25.4% effect on psychomotor learning outcomes. This model effectively improves learning outcomes while fostering environmental awareness in accordance with the principles of the Independent Curriculum.  Keywords: Project-Based Learning, Student Learning Outcomes, Islamic Religious Education